Why agents need discretion: The business judgment rule as optimal standard of care - Andreas Engert; Susanne Goldlücke (University of Mannheim, Department of Economics, 2013)
Should managers be liable for ill-conceived business decisions? One answer is given by U.S. courts, which almost never hold managers liable for their mistakes. In this paper, we address the question in a theoretical model of delegated decision making. We find that courts should indeed be lenient as long as contracts are restricted to be linear. With more general compensation schemes, the answer depends on the precision of the court's signal. If courts make many mistakes in evaluating decisions, they should not impose liability for poor business judgment.
urn:nbn:de:bsz:180-madoc-329593
Keywords: K13; K22; M53; 330; business judgment rule; manager liability; delegated decision-making